ICSID and new trends in international dispute settlement. - PARRA, Antonio R. (1993)
Reviews the work of ICSID in the settlement of disputes. Notes that until the mid-1980s, jurisdiction in all cases was founded upon consents to arbitration recorded by a clause in a single instrument. Since then, the Centre has registered cases where there is no such contract between the parties and where jurisdiction was based on arbitration provisions, in investment legislation of the State party or on consent to arbitration recorded in bilateral investment promotion and protection treaties.